Menumbuh Kembangkan Rasa Nasionalisme dalam Menjunjung Patriotik Kebangsaan Bagi Masyarakat Indonesia - Lbn. Raja, Edward A.; Lbn. Raja, John Gilber; Lbn. Raja, Togu Harlen (Akademi Farmasi YPPM Mandiri, 2023)
Nationalism is not a new thing in this world where nationalism has existed since ancient times where a sense of brotherhood and a sense of concern for one another has occurred since ancient times. Nationalism arises from the existence of differences among humans, whether there are differences in ethnicity, religion, clan which are used as glue for human relations. A good relationship will be maintained by a high sense of brotherhood among human beings. The State of Indonesia has many differences including thousands of tribes, languages, customs and religions so that this needs to be maintained as a wealth in the Unitary State of the Republic of Indonesia. Pancasila as the basis of the State and UUD 1945 as the foundation of national and state life have regulated the pattern of human life and explained the relationship between a good sense of justice in Indonesian society.